Fostering Environmental Responsibility in U.S. K-12 Education: A Comparative Study of Strategies Integrating STEM - Aleks Matevos Vartanian (Journal of Advanced Research in Education, 2024)
This review explores the integration of STEM education with a focus on environmental responsibility in U.S. K-12 settings. Examining case studies, theoretical frameworks, and best practices, the paper emphasizes the transformative potential of this approach. The theoretical foundation conceptualizes environmental responsibility in education, emphasizing the connection between STEM concepts and real-world environmental challenges. The literature review traces the historical evolution of environmental education in U.S. K-12 schools, highlighting the urgency for transformative approaches like STEM integration. Comparing STEM integration strategies through case studies underscores the importance of a holistic approach, including interdisciplinary curricula, project-based learning, professional development, sustainable initiatives, and community engagement. Derived best practices offer practical guidance, emphasizing ongoing professional development, curricular alignment, project-based learning, resource allocation, community engagement, and collaboration. These recommendations form a roadmap for effective STEM integration with environmental responsibility. In conclusion, this review highlights the transformative potential of STEM integration in fostering environmentally responsible citizens. By embracing these principles, educational institutions can cultivate a generation capable of addressing complex environmental challenges, ensuring a sustainable and resilient future.